Optimization and application of the carrier DNS data analysis technology - Wei PENG; Xiaodong HE; Xiaoming LU; Chuanxin JI (Dianxin kexue)
The principles of DNS data analysis and the limitations of traditional DNS data analysis method were analyzed.According to the trend of the development of the IP network,an analysis technology based on the Hadoop towards huge amounts of DNS data was proposed.Also the architecture,implementation scheme and advantages of the technology scheme were described,then the effect of Hadoop DNS data analysis which applied in the telecom network was expounded.The research results can provide scientific reference for the development and optimization of the telecom network.